Disclosure Practices of Listed Philippine Mining Companies, 2006-2010 - Siy, Jay Stephen (Philippine Management Review; Vol 20 (2013), 2013)
The paper examines the disclosure practices of seventeen listed mining companies in the Philippines focusing on two frameworks: mineral and financial reporting.  A comparative study of the annual reports of listed mining companies is performed from 2006 to 2010.  The period of analysis is significant following major developments in public reporting.  Chief among them is the implementation of the Philippine Financial Reporting Standard 6 in 2006 and the adoption of the Philippine Mineral Reporting Code in 2007.  The findings indicate reduced comparability as a result of: (1) non-compliance with the mineral reporting code; (2) non-disclosure of mineral assets; (3) varying treatments of exploration and evaluation costs; and, (4) inconsistent mineral and ore category definitions as a result of weak integration between the frameworks.  These public reporting issues prevent meaningful assessment by users undermining investment attractiveness and the ability of mining companies to communicate their performance and potentials.